Hyperbole: A Pragmatic Perspective - Saffah, Mariam (Advances in Social Sciences Research Journal, 2021)
Unlike most previous studies which investigate hyperbole in literary contexts, the present review tries to portray it as an interactional pragmatic phenomenon occurring in everyday conversations. The listener’s awareness that there is a difference between what is said and what is meant is essential for the recognition of hyperbole. Therefore, context is crucial for interpreting hyperbolic utterances. As a pragmatic notion, hyperbole has not been given its due attention. Hence, this review attempts to bridge this gap in the literature through answering the following questions: What are the functions, types, and forms of hyperbole? What is the relationship between hyperbole and other notions such as irony? And how it can be used as persuasive device?